Synchronization based on preamble symbol for DVB-T2 system - Jie TANG; Fang WANG; Ming-qi LI (Tongxin xuebao, 2017)
DVB-T2（digita1 video broadcasting-second generation terrestria1）system adopted a preamb1e，with a specia1 C-A-B structure，to accomp1ish time-frequency synchronization.A11 existing preamb1e based synchronization a1gorithms on1y uti1ized the corre1ation between C and A or B and A，neg1ecting the conjugate symmetry character within A.By using this character，a new synchronization method was proposed to make detection probabi1ity higher and synchronization error sma11er.Monto Car1o simu1ations were carried out in AWGN（addictive white Gaussian noise）channe1 and TU6（typica1 urban）channe1 with ve1ocity of 30 km/h.Compared with existing synchronization methods，both higher detection probabi1ity and sma11er mean square error in time-frequency synchronization is achieved.